Digital Agriculture Profile: Ethiopia - Tamene, Lulseged D.; Ashenafi, Ali (2022)
Improving agricultural productivity in Ethiopia is crucial to alleviate poverty and meet growing food demand amid environmental stress and climate change. Agricultural innovation and access to digital agricultural solutions have the potential to boost productivity while reducing negative environmental footprints in agriculture and food system value chains. However, most smallholder farmers in Ethiopia have limited access to digital farming solutions. A disruptive approach is required to overcome crises in the sector and boost productivity to meet ecosystem needs and the related service demands of a growing population. Digital readiness is crucial to embrace and deploy existing technologies and transform agriculture. There are several challenges hampering the development of digital agriculture in Ethiopia. Access to advanced agricultural, knowledge, and information technologies is constrained due to weak digital infrastructure and facilities in the country. This includes limited data sharing policies and implementation guidelines to facilitate the collection and storage of, and access to, data to support digital solutions. The low digital literacy rate is another barrier to the expansion of ICT -based agricultural extension and consulting services. The majority of farmers have limited technical capacity to adopt digital services and products. Limited financing to support the launch and upscaling of digital products and services limits the advancement of digital agriculture in Ethiopia. This document summarizes the key potentials, constraints and enabling environments needed to transform agriculture through digital solutions. It also attempts to map the key actors who are engaged in the development of different 'digital products' that can support agriculture.